Inventarisasi Famili Ericaceae Di Taman Wisata Alam Danau Sicikeh-Cikeh Desa Lae Hole Kecamatan Parbuluan Kabupaten Dairi Sumatera Utara - Fitri Asyiah Lubis; Kartika Manalu; Rahmadina Rahmadina (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2020)
ABSTRACTThe Ericaceae family has benefit as medicines and ornamental plants, because several types of the Ericaceae family have very attractive colors, fruits and flower shapes, besides that they have important ecological and economic values. This study aims to determine the types and morphology of the Ericaceae family in the Sicikeh-cikeh Lake Nature Tourism Park Lae Hole Village Parbuluan District Dairi Regency Sumatera Utara. This research were conducted in October - January 2020 using the exploration methods, namely by exploring along the path of the research location. The results of studies that have been carried out found 7 types of family Ericaceae, such as 4 of the genus Rhododendron, 1 of the genus Vaccinium, 1 of the genus Diplycosia, and 1 of the genus Cavendishia. The types of the Ericaceae family were found in this study had the same morphology, which has a taproot. The shape of the stem was round, and the direction grows perpendicular (erectus). The leaves are single leaves. Flowers including majmuk flowers, (terminal), and has flower parts, namely the crown of flowers, stamens and pistil. The fruit had a capsule and buni fruit. Keywords : Inventory, Ericaceae Family, Morphology, Sicikeh-cikeh Lake Nature Tourism Park